Direct Detection and Identification of the Most Common Bacteria and Fungi Causing Otitis Externa by a Stepwise Multiplex PCR - Aboutalebian, Shima; Ahmadikia, Kazem; Fakhim, Hamed; Chabavizadeh, Javaher; Okhovat, Ahmadreza; Nikaeen, Mahnaz; Mirhendi, Hossein (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Considering the importance of differential diagnosis of infectious otitis externa (OE), a stepwise PCR based assay with universal primers and genus or species specific primers for the detection/identification of the most prevalent bacterial and fungal etiologies of OE were developed and evaluated on ear aspiration specimens of clinically suspected patients. Methods and Materials: A total of120 ear aspiration specimen with otomycosis suspicion was subjected to manual DNA extraction using phenol-chloroform-isoamyl extraction after tissue digestion with lysis buffer. The multiplex PCR was initially done using pan-fungal and bacterial homemade primers. For identification of bacterial genera, Pseudomonas and Staphylococcus specific primers were simultaneously used in one reaction mixtures. For identification of fungal agents, Candida species specific multiplex primers targeting the most clinically important Candida species causing OE, namely C. albicans, C. parapsilosis and C. auris and Aspergillus related multiplex PCR identifying the most prevalent Aspergillus species were used in two separate reaction mixtures. All the result of multiplex PCR was interpreted based on amplicon size. Results: The overall multiplex PCR-based detection rate of bacterial (88 specimens, 73.3%) and fungal (97 specimens, 81%) OE documented to be as 100% and complete consistency with the results of direct examinationand Giemsa staining were recorded. In 76 specimens (63.3 %) double amplicon bands pertaining to bacterial and fungal pathogens were evidenced. The positivity rate of pan-fungal PCR was higher than culture result. Of the 88 pan-bacterial positive PCR specimens, 66 and 47 were positive for Staphylococcus and Pseudomonas, respectively. Thirty samples exhibited mixed infection of both. However, 5 specimens remained negative. Of the 97 pan-fungal positive PCR specimens, 67 and 51 specimens showed to contain Candida andAspergillus species, respectively. In thirty specimens, dual amplicon bands of Candida and Aspergillus related multiplex PCR were yielded. Conclusion The stepwise multiplex PCR assay proved to be more sensitive than culture, more rapid, less cumbersome in detection and identification of fungal and bacterial OE